SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN AKREDITASI PUSKESMAS DENGAN METODE ANALYTIC HIERARCHY PROCESS (AHP) PADA DINAS KESEHATAN KABUPATEN SANGIHE - Lendri A. Garing; Stenly C. Takarendehang; Abraham Kamal (Pusat Penelitian dan Pengabdian kepada Masyarakat, POLITEKNIK NEGERI NUSA UTARA, 2018)
Each every Puskesmas archipelago Sangihe need the assessment accredit as conducting public and quality institution. The reaching of accredit the A from Body Accredit the National is not easy matter in a short time. Limitation of human resource, time, fund and TIRE assessment making as consideration each every head on duty health for the repair of accreditation. System of Decision Supporter made to assist the head on duty health in menyususn of repair priority seven standard accredit pursuant to consideration of condition Puskesmas. Method of Analytic Process Represent one of method form capable to elaborate a problem to form hierarki by level. Software which is developing to use the Ianguage of pemograman QT CREATOR and its data bases use the MYSQL . Hence require to be develop builded a computerized system which can assist the team accredit from town regency and also from provinsi in determining elegibility accredit Puskesmas. By develop building system of supporterof elegibility decision accredit the Puskesmas with the method AHP can assist in decision determination in taking decision and determine precisely and competent accurate accredit and not accredit.